The Contextual Effect of Village on Early Marriage in Wonogiri, Central Java - Prawita, Mirna; Soemanto, RB; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: In spite of international agreements and national laws, the marriage of girls <18 years of age is common worldwide and affects millions. Child marriage is a human rights violation as it prevents girls from obtaining an education, enjoying optimal health, bonding with others their own age, maturing, and ultimately choosing their own life partners. Child marriage is driven by poverty. Therefore, village level of prosperity may have a contextual effect on child marriage. The purpose of this study was to examine the contextual effect of the village on early marriage in Wonogiri, Central Java. Subjects and Method: A case-control study was conducted at 25 villages in Wonogiri, East Java, in December 2018. A sample of 225 women was selected by fixed disease sampling. The dependent variable was an early marriage. The independent variables were the intention, attitude, perceived behavior control, paternal education, maternal education, and information exposure. The data were collected by questionnaire and analyzed by multilevel analysis. Results: The risk of early marriage increased with exposure to negative information (b= 0.97; 95% CI= 0.20 to 1.72; p<0.012), negative attitude (b= 1.67; 95% CI= 1.00 to 2.67; p<0.001), and strong intention (b= 1.86; 95% CI= 1.03 to 2.70; p<0.001). The risk of early marriage decreased with high paternal education (b= -0.81; 95% CI= -1.57 to -2.14; p= 0.009), high maternal education (b= -0.65; 95% CI= -1.37 to 0.85; p= 0.083), strong perceived behavior control (b= -1.77; 95% CI= -1.77 to -0.20; p= 0.013). Village had contextual effect on early marriage with ICC= 15%. Conclusion: The risk of early marriage increases with high exposure to information, negative attitude, and strong intention. The risk of early marriage increases with high paternal education high maternal education, strong perceived behavior control. The village has a contextual effect on early marriage. Keywords: intention, early marriage, parental education, information exposure Correspondence: